Justification of conceptual approaches to producing energy without energy carrier consumption - Vorobiov , Oleh; Uhrynovych , Oleh; Klontsak , Mykola; Kondratiuk, Serhii (Social Development and Security, 2021)
The article is devoted to solving the problems of providing energy to industrial sectors and objects, vehicles, personal needs of a person and, in general, energy security of future generations of mankind.An analysis of scientific works in this area is carried out and it is determined that the stake is placed on the extraction and use of alternative types of energy, which is not able to meet the ever-increasing needs of mankind.Conceptual approaches to energy production are proposed based on the scientific hypothesis of energy production without the consumption of energy carriers. In this case, traditional thermal, electrical, gravitational, light, sound, wind, hydraulic, biological and other types of energy are only ways of transferring, transporting energy, and not energy itself. Energy is characterized by the values of the vibrational parameters of the radiation waves and the occupied space with a certain energy density.On the basis of these approaches, the fuel is activated, it is energized, that is, the energy efficiency is increased by the heat of the exhaust gases. Depending on the types of fuels and devices where they are used, with the same final result, the consumption of energy carriers can be reduced by 10 - 80%. This ensures complete combustion of each individual fuel component. At the same time, not only energy problems are being solved, but also very complex environmental problems.In the future, it is proposed to substantiate the requirements for devices for converting energy types for these promising engines.